Colonic perforation in a kidney recipient with Cytomegalovirus (CMV) colitis - F Oliaei (Babol University of Medical Sciences, 2005)
Background and Objective: Gastrointestinal (GI) involvement is a cause of morbidity and mortality in kidney transplant recipients. Patients are at risk of GI infections during 1-6 months after transplantation. The major viral pathogen involving GI tract in transplanted patients is CMV. The incidence of active disease in seropositive patients is about 25%. There is a significant increase in mortality of kidney recipients suffering GI disease with CMV. Case: A 58-year-old man hospitalized with weakness and confusion three weeks after kidney transplantation. Gradually LLQ (Left lower quadrants) tenderness appeared. Abdominal X-ray showed subdiaphragmatic air. Sigmoidal perforation was revealed after abdominal laparotomy. CMV-PCR (Polymerase chain reaction) from blood was positive and CMV colitis was confirmed by colonic biopsy. Ganciclovir and broad-spectrum antibiotics were started but he died 5 days later because of sepsis. Conclusion: CMV disease may be fatal in kidney recipients. Despite severe disease, there may be just a few signs and symptoms. So, there must be a high index of suspicion in kidney recipients during first 6 months after transplantation.